A comparison of SNARF-1 and skeletal δ 11 B estimates of calcification media pH in tropical coral - Allison, Nicola; Venn, Alex; Tambutte, Sylvie; Tambutte, Eric; Wilckens, Frederike; Kasemann, Simone (Geochimica et Cosmochimica Acta, 2023)
Coral skeletal boron geochemistry offers opportunities to probe the pH of the calcification media (pHCM) of modern and fossil specimens, to estimate past changes in seawater pH and to explore the biomineralisation response to future ocean acidification. In this research we grew 2 Stylophora pistillata coral microcolonies over glass coverslips to allow analysis of the pH sensitive dye SNARF-1, in the extracellular calcification medium at the growing edge of colonies where the first aragonite crystals are formed, under both light and dark conditions. We use secondary ion mass spectrometry (SIMS) to measure the boron isotopic composition (δ 11 B) of the skeleton close to the growth edge after 2 to 3 days of additional calcification had enlarged the crystals until they joined, generating a continuous sheet of aragonite. Mean skeletal δ 11 B-pHCM estimates are higher than those of by SNARF-1 by 0.35 to 0.44 pH units. These differences either reflect real variations in the pH of the calcification media associated with each measurement technique or indicate other changes in the biomineralisation process which influence skeletal δ 11 B. SNARF-1 measures directly the pH of the extracellular calcification medium while skeletal δ 11 B analyses aragonite potentially formed via both extracellular and intracellular biomineralisation pathways. Analysis of a third coral specimen, also growing on a glass slide but with a 5 cm long branch, indicated good agreement between the δ 11 B value of the apex of the branch and the skeletal growth edge. The tissues overlying both these regions were transparent indicating they had low symbiont densities. This suggests that the biomineralisation process is broadly comparable between these sites and that studies growing corals over glass slides/coverslips provide representative data for the colony apex.